A Conceptual Model for Planning and Management of Areas of Public Space and Meeting in Colombia - Juan Jiménez-Caldera; José Luis Serrano-Montes; Raúl Pérez-Arévalo; Jesús Rodrigo-Comino; Luca Salvati; Andrés Caballero-Calvo (Land, 2022)
A refined investigation of new trends in urban analysis assuming a sustainable design of Areas of Public Space and Meeting (APSM) is a fundamental response to the challenges of inclusive and efficient cities. Even though the APSM are districts regarded as urban structuring systems, there is a lack of territorial planning instruments and conceptual models aimed at explaining their long-term dynamics. Based on these premises, we developed a conceptual model that articulates relevant variables of interest for the planning and management of APSM. The construction of the model includes the review and analysis of the literature and the validation process based on a consultation with a panel of experts on the subject. Our findings demonstrate that the existing research does not address the APSM issue adequately, and the methodologies proposed so far do not lead to accurate and comprehensive analyses of urban complexity in light of sustainability targets. There are only isolated, disjointed, and partial approaches to variables of interest, making it difficult to carry out holistic studies. Our technical and scientific proposal offers a framework for an exhaustive evaluation of these areas. The model has been structured according to the assumptions of urban sustainability and can be applied to diverse urban environments in South America.